Impacto de intervenção educativa com apoio de módulo educacional sobre segurança do paciente em anestesiologia - Maranhão, Kariny Sheyla Rodrigues (2024)
Introduction: The competency matrix of the Medical Residency Programs in Anesthesiology in Brazil has the specific objective of “performing anesthesia safely in all its stages”, whose elements for the implementation of a specific curriculum need to be defined. Given this scenario, the development and implementation of an educational module on patient safety for anesthesiology residents was proposed. Objectives: To evaluate the impact of an educational intervention, supported by an educational module on patient safety in anesthesiology, on residents' knowledge of the specialty and their degree of satisfaction with the strategy developed. Methods: Quasi-experimental study with an interrupted time series design with a group, carried out at the Hospital Universitário Onofre Lopes (HUOL), of the Federal University of Rio Grande do Norte (UFRN), involving 10 residents from the first to the third year of the Medical Residency Program of Anesthesiology at the Institution. An educational module was developed, in e-book format, and a pedagogical strategy was implemented to mediate the learning of residents, in four face-to-face meetings, which took place during practical activities at the hospital. A knowledge assessment was carried out with a pre-test, before the first discussion of patient safety content, in the first meeting, and post-test, in the last meeting, and satisfaction assessment using a questionnaire with a Likert scale. Results: Pre-test scores ranged between 6.25 and 8.75 (average 7.50), while posttest scores ranged from 7.50 to 10.0 (average 9.03). A significant difference was found for the values of the median scores in the two moments of application of the test, using the Wilcoxon test, at the significance level α = 5% (p- value: 0.0199). The consistency of the satisfaction questionnaire was assessed using Cronbach's alpha coefficient (alpha of 0.793), being considered “Acceptable”. In general, the answers were satisfactory for each of the items questioned, with all of them varying between “Agree” and “Totally Agree”. Conclusion: The development and implementation of an educational module to mediate learning, during the training process of anesthesiology residents, were effective in promoting knowledge about patient safety for anesthesiologists in training, with high levels of satisfaction. Thus, the importance of including the topic of Patient Safety in the curricular structure of residency courses in anesthesiology is highlighted, with protected space and time for the learning process of these professionals. Furthermore, more studies are needed that can measure the long-term impact of this intervention, its influence on the acquisition of skills and whether these educational interventions improve outcomes for patients.